ANALISIS PENGARUH TOTAL QULITY MANAGEMENT DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DENGAN KINERJA KARYAWAN SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Puskesmas Ungaran di Kecamatan Ungaran Barat) - Kartiko Aji, Hapsoro; Arfianto, Erman Denny (Diponegoro Journal of Management, 2018)
This research is based on previous inconsistent research about Total Quality Management and Quality of service to customer satisfaction directly or indirectly that cause research gap (research gap). This study aims to test the Total Quality Management and service quality to customer satisfaction by including new variables as moderation of performance.               This research was conducted in one of public functional unit of public sector ie Ungaran Health Center. Data collection method used is with the distribution of questionnaires to patients Puskesmas Ungaran as many as 111 respondents. The method of analysis yag used is the method of multiple regression analysis. The result of this research yield 2 regression equation as follows: Y1 = 0,293 X1 + 0,562 X2 and Y2 = 0,440 Y1 – 0,075 X1 + 0,534 X2.            Based on the analysis of statistical data, the indicators in this study successfully passed in the validity and reliability test so that the data can be said to be valid and reliable. In the classical assumption test and multiple regression in the first and second equations show the normal distribution and not affected by heteroskedatisitas. In the Sobel test also found that intervening variable successfully moderate the independent variable to the dependent variable. The results showed that all independent variables have positive and significant influence on the intervening variable and dependent variable directly except there is 1 independent variable that is TQM which negatively and insignificant to customer satisfaction directly.